2006
DOI: 10.1152/ajpcell.00379.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacidity of secreted fluid from submucosal glands in early cystic fibrosis

Abstract: Prior studies have shown that fluid secretions from airway submucosal glands in cystic fibrosis (CF) are reduced and hyperviscous, possibly contributing to the pathogenesis of CF airway disease. Because the CF transmembrane conductance regulator (CFTR) protein can transport both chloride and bicarbonate, we investigated whether gland fluid pH is abnormal in early CF, using nasal biopsies from pediatric subjects having minimal CF lung disease. Gland fluid pH, measured in freshly secreted droplets under oil stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
171
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(188 citation statements)
references
References 42 publications
15
171
0
2
Order By: Relevance
“…Studying a porcine model of cystic fibrosis (CF) (37,38), we found that loss of cystic fibrosis transmembrane conductance regulator (CFTR) anion channels reduced HCO 3 − secretion and decreased ASL pH (39,40), results consistent with earlier findings in human airway epithelia (41)(42)(43)(44). Importantly, the abnormally acidic pH partially inhibited bacterial killing by ASL (40).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Studying a porcine model of cystic fibrosis (CF) (37,38), we found that loss of cystic fibrosis transmembrane conductance regulator (CFTR) anion channels reduced HCO 3 − secretion and decreased ASL pH (39,40), results consistent with earlier findings in human airway epithelia (41)(42)(43)(44). Importantly, the abnormally acidic pH partially inhibited bacterial killing by ASL (40).…”
supporting
confidence: 87%
“…In cultured human and porcine airway epithelia, in vitro studies of airways, and in vivo studies in newborn piglets and neonatal humans, CF ASL is abnormally acidic (40,(42)(43)(44), consistent with the loss of CFTR-dependent HCO 3 − transport (39,41). However, in older children and adults with CF, the effect of genotype in ASL pH is more variable (44,58,74).…”
Section: Discussionmentioning
confidence: 86%
“…These defects decrease the rate of liquid secretion by submucosal glands and reduce the pH of the secreted liquid (30,31,35). We found that blocking Cl − secretion and eliminating HCO 3 − secretion in non-CF airways reproduced some of the abnormalities of CF airways.…”
Section: Muc5b Forms Mucus Strands and Muc5ac Forms Mucus Threads Andmentioning
confidence: 64%
“…ASL pH was measured using the pH-sensitive fluorophore BCECF conjugated to 10 kDa dextran (Invitrogen) as described elsewhere (40), which was added 4 to 6 h before measurement (20 ml of 0.5 mg/ml in PBS). Cell inserts were incubated in HCO 3…”
Section: Asl Depth and Ph Measurementsmentioning
confidence: 99%